Isleria, a new genus of antwren (Aves: Passeriformes: Thamnophilidae) - Bravo, Gustavo A.; Chesser, R. Terry; Brumfield, Robb T. (Zootaxa, 2012)
A comprehensive molecular phylogenetic analysis of the family Thamnophilidae indicated that the genus Myrmotherula is not monophyletic. The clade composed of M. guttata and M. hauxwelli is only distantly related to other members of the genus and should be removed from Myrmotherula. The phenotypic distinctiveness of the clade argues against merging it with its sister group Thamnomanes and no generic name is available for the guttata-hauxwelli clade. Consequently, we describe the genus Isleria for these two species, and designate Myrmothera guttata as its type species.